Propriedades antimicrobianas, físico-mecânicas e de liberação de fluoreto do cimento de ionômero de vidro associado ao hexametafosfato de sódio microparticulado e nanoparticulado - Hosida, Thayse Yumi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to evaluate antimicrobial, physico-mechanical and fluoride release properties of the glass ionomer cement (GIC) associated with HMP microparticle and nanoparticle. Initially, solutions of HMP were obtained at concentrations of 1, 3, 6, 9 and 12 %, and the antibacterial activity was evaluated against Streptococcus mutans, Lactobacillus acidophilus and Actinomyces israelli by agar diffusion test. The same methodology was used to determine the antimicrobial activity of GIC associated with HMP at concentrations of 6, 9 and 12 % microparticle or nanoparticle. The release of F and HMP were determined in demineralization and remineralization solutions. Furthermore, the resistance to diametral tensile and compression, surface hardness and the degree of conversion of monomers were measured. Parametric and non-parametric tests were performed, after checking homocedasticity data (p < 0.05). The solutions of 6, 9 and 12 % of HMP showed better antimicrobial activity against all bacteria tested, and these concentrations incorporated into the CIV. All concentrations of HMP incorporated into the GIC had antimicrobial activity for all bacteria. There was a dose-response relationship between concentration of HMP in the GIC and antimicrobial activity. Regarding the release of F and HMP, higher values occurred on the first day in all groups and the highest levels of release occurred in groups containing 9 and 12 % of HMP nanoparticle. However the incorporation of HMP in the GIC reduced values of physical and mechanical tests when compared to the GIC, showing a dose-response relationship. It was concluded that the incorporation of HMP in GIC improves antimicrobial activity and increase the release of fluoride, but reduces its physical and mechanical properties. The reduction of particulate HMP led to better antimicrobial and fluoride release results

O objetivo do presente estudo foi avaliar as propriedades antimicrobianas, físico-mecânicas e de liberação de fluoreto do cimento de ionômero de vidro (CIV) associado ao hexametafosfato de sódio (HMP) microparticulado e nanoparticulado. Inicialmente, foram obtidas soluções de HMP nas concentrações 1, 3, 6, 9 e 12 % e a atividade antibacteriana foi avaliada contra Streptococcus mutans, Lactobacillus acidophilus e Actinomyces israelli por meio do teste de difusão em ágar. A mesma metodologia foi empregada para determinar a atividade antimicrobiana do CIV associado ao HMP nas concentrações de 6, 9 e 12 % microparticulado ou nanoparticulado. Foi determinada a liberação de fluoreto (F) e HMP em soluções de desmineralização e remineralização. Além disso, as resistências à tração diametral e compressão, dureza de superfície e grau de conversão de monômeros foram analisados. Testes paramétricos e não paramétricos foram realizados, após a verificação da homocedasticidade dos dados (p < 0,05). As soluções de 6, 9 e 12 % de HMP apresentaram melhor atividade antimicrobiana contra as bactérias testadas, sendo essas concentrações incorporadas ao CIV. Todas as concentrações de HMP associado ao CIV tiveram atividade antimicrobiana para todas as bactérias. Observou-se uma relação dose-resposta entre concentração de HMP no CIV e a atividade antimicrobiana. Com relação à liberação de F e HMP, os maiores valores ocorreram no primeiro dia em todos os grupos e as maiores médias de liberação ocorreram nos grupos contendo 9 e 12 % de HMP nanoparticulado. Entretanto, a incorporação do HMP ao CIV reduziu as propriedades físico-mecânicas quando comparado ao CIV mostrando uma relação dose-resposta. Concluiu-se que a incorporação de HMP no CIV melhora a atividade antimicrobiana e aumenta a liberação de F, porém reduz suas...
Keywords: Cimentos de ionômeros de vidro; Fosfatos; Nanopartículas; Polimerização; Agentes antibacterianos; Força compressiva; Dental glass ionomer cements